2022
DOI: 10.1097/md.0000000000029970
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the neutrophil-to-lymphocyte ratio as a new simple biomarker of adult onset Still’s disease: A STROBE-Compliant prospective observational study

Abstract: This study was performed to investigate the role of neutrophil-to-lymphocyte ratio (NLR) in the diagnosis of adult onset Still disease (AOSD) and its performance to improve the sensitivity of the classifications criteria (Yamaguchi and Fautrel Classifications). We conducted a multicenter prospective nationwide case-control study in Internal medicine, Rheumatology and Infectious disease departments, to include successively patients with suspected AOSD (2 or more major criteria of Yamaguchi or Fautrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…16,17 In recent years, NLR has been found to predict the activity and prognosis of rheumatic diseases (including GA). [17][18][19][20][21] This review summarizes existing evidence on the relationship between NLR and GA, evaluates whether NLR can guide clinical measures, explores the potential pathophysiological mechanisms of NLR, and thereby provides a foundation for future research.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In recent years, NLR has been found to predict the activity and prognosis of rheumatic diseases (including GA). [17][18][19][20][21] This review summarizes existing evidence on the relationship between NLR and GA, evaluates whether NLR can guide clinical measures, explores the potential pathophysiological mechanisms of NLR, and thereby provides a foundation for future research.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study by Jung et al 69 identified that chemokine (C-C motif) ligand 2 levels in serum correlated with systemic score, leukocyte and neutrophil counts, and CRP, ferritin, lactate dehydrogenase, and albumin levels in patients with AOSD. A prospective observational study 70 validated the neutrophil-to-lymphocyte ratio (NLR) of ≥4 as a biomarker of AOSD, with a sensitivity of 93.8%. The authors observed that the addition of NLR to the Yamaguchi and Fautrel classifications as a major criterion significantly improved their sensitivity while maintaining specificity.…”
Section: Still’s Disease Continuummentioning
confidence: 99%
“…The increase in neutrophil count is another typical hallmark of AOSD. A recent observational study identified the neutrophil-to-lymphocyte ratio (cut-off value of ≥ 4) as a promising biomarker of AOSD with a high sensitivity, and that could replace the neutrophil percentage (≥ 80%) in the classification criteria [ 60 ]. Serum calprotectin (a heterodimer of the S100A8 and S100A9 proteins) belongs to the S100 family proteins (S100A8, A9, A12), a group of calcium-binding proteins also called calgranulines.…”
Section: Supporting Diagnosis: Old and New Biomarkers And The Role Of...mentioning
confidence: 99%